Corporate governance and current regulation in the German banking sector: an overview and assessment - Matthias Köhler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
This paper gives an overview over corporate governance and banking regulation in Germany. Particular attention is put on legal and regulatory changes that were made in response to the financial market crisis. The paper shows that the changes mainly focus on the remuneration of managers and on further professionalizing the supervisory board. Problematic is that several laws that were enacted in the past years to improve corporate governance focus on listed firms. Furthermore, some of the recommendations and suggestions made to improve corporate governance in Germany are not legally binding even for stock corporations. Recent empirical evidence, moreover, suggests that bank shareholders pushed for greater risk-taking and not managers. This contrast with public view that the bank managers are pushed by aggressive remunerations schemes to increase risk-taking and indicates that the recent legal and regulatory changes fail to remove all weaknesses of the German corporate governance system.
Keywords: G21; G34; G38; 330; Corporate governance; banks; regulation; remuneration schemes; supervisory board; Bank; Corporate Governance; Bankenpolitik; Vergütungssystem; Aufsichtsrat; Shareholder Value; Bankrisiko; Deutschland